2022
DOI: 10.1039/d2ob00234e
|View full text |Cite
|
Sign up to set email alerts
|

Who stole the proton? Suspect general base guanine found with a smoking gun in the pistol ribozyme

Abstract: The pistol ribozyme (Psr) is one among the most recently discovered classes of small nucleolytic ribozymes that catalyze site-specific RNA self-cleavage through 2′-O-transphosphorylation. The Psr contains a conserved guanine (G40)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…We have previously reported computational simulations for the HHr, Psr, , 8–17dz, and VSr systems, and also made cross-cutting studies of the role of the divalent metal ion in promotion of productive hydrogen bonding of the O2′ nucleophile to facilitate its activation . The details of the system setup, convergence of the simulations, and other specialized analysis can be found in these other works.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported computational simulations for the HHr, Psr, , 8–17dz, and VSr systems, and also made cross-cutting studies of the role of the divalent metal ion in promotion of productive hydrogen bonding of the O2′ nucleophile to facilitate its activation . The details of the system setup, convergence of the simulations, and other specialized analysis can be found in these other works.…”
Section: Methodsmentioning
confidence: 99%
“…To gain further insights into the Dz's mode of action, future MD studies may consider (a) the use of molecular solvation theory to predict water and metal ion binding sites in nucleic acids [47] or (b) treating the catalytic centre at the quantum mechanical level while using a molecular mechanics representation of the rest of the system or (c) using a deprotonated catalytic base to represent the state of attack better [30,31,48]. However, these methods generally work best in conjunction with an X-ray crystal structure of the DNAzyme that includes co-crystallised metal ions at the catalytic centre.…”
Section: Catalysismentioning
confidence: 99%
“… [60] Under the assumption of a local rearrangement (into a L‐platform/L‐scaffold framework) simulated by molecular dynamics calculations, G42 has been proposed to act as general base in a primary catalytic pathway. [60] Having the c 1 G modification in hands, we set out to experimentally test this hypothesis with the corresponding G42c 1 G mutant. We found that the cleavage rate for the mutated ribozyme was 0.89±0.06 min −1 which is only 4.2‐fold slower compared to the wildtype ribozyme (Supporting Figure S11, Supporting Table S3).…”
Section: Resultsmentioning
confidence: 99%